Characterisation of fragrance major compouds in intact plant and in vitro cultures of Citrus grandis (Osbeck) flowers - Mohd Azlan, Mohd Ishak; Zarina, Zakaria; Abd Hamid, Khalid; Suhana, Zakaria (Universiti Teknologi MARA (UiTM), 2008)
Organized by Institute of Research, Development and Commercialisation (IRDC), UiTM, 3rd - 5th July 2007 at Sunway Lagoon Resort Hotel, Selangor.